The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/iai.73.1.546-551.2005
|View full text |Cite
|
Sign up to set email alerts
|

Replication Dynamics of Mycobacterium tuberculosis in Chronically Infected Mice

Abstract: The dynamics of host-pathogen interactions have important implications for the design of new antimicrobial agents to treat chronic infections such as tuberculosis (TB), which is notoriously refractory to conventional drug therapy. In the mouse model of TB, an acute phase of exponential bacterial growth in the lungs is followed by a chronic phase characterized by relatively stable numbers of bacteria. This equilibrium could be static, with little ongoing replication, or dynamic, with continuous bacterial multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
152
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 34 publications
7
152
0
Order By: Relevance
“…Silencing of prcBA transcription during mouse infections demonstrated that the Mtb proteasome is not only required for optimal in vivo growth but is also essential during the chronic phase of the infection, when the pathogen replicates slowly or not at all 31,32 . The eukaryotic proteasome participates in protein turnover, transcription and DNA repair 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of prcBA transcription during mouse infections demonstrated that the Mtb proteasome is not only required for optimal in vivo growth but is also essential during the chronic phase of the infection, when the pathogen replicates slowly or not at all 31,32 . The eukaryotic proteasome participates in protein turnover, transcription and DNA repair 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the pathogen as well as host immunity may significantly alter TB morbidity and virulence over a relatively short period of time (Palkovich, 1981). In particular, murine models suggest that the chronic slow progression of TB is not due to slow replication of the bacterium itself, but to the ability of the localized immune response to maintain equilibrium and latency (Munoz-Elias et al, 2005;Ulrichs et al, 2005;Gill et al, 2009). There is also clinical evidence suggesting that the host response plays a major role in restricting intracellular mycobacterial growth and therefore in determining the clinical manifestations of the disease (Schluger and Rom, 1998).…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…In the i.v. infection model, bacteria replicate exponentially in the lungs for the first 2 wk postinfection; thereafter, bacterial numbers remain relatively stable for several months (6)(7)(8). From 4 wk onward, half of the mice were treated with INH.…”
Section: Tuberculosis Persistence Mutantsmentioning
confidence: 99%
“…Although these drugs rapidly kill Mycobacterium tuberculosis grown in vitro, they are less active against bacteria grown in vivo in mammalian hosts (4,5). In the mouse model of TB, infection progresses through a brief acute phase, when bacteria replicate exponentially in the lungs, to a protracted chronic phase, when growth slows and bacterial numbers are stabilized by the immune response (6)(7)(8). Anti-TB drugs like INH display good bactericidal activity in acutely infected mice, but chronic infection is more refractory (9).…”
mentioning
confidence: 99%